2017
DOI: 10.3233/jad-160677
|View full text |Cite
|
Sign up to set email alerts
|

Amylin Treatment Reduces Neuroinflammation and Ameliorates Abnormal Patterns of Gene Expression in the Cerebral Cortex of an Alzheimer’s Disease Mouse Model

Abstract: Our recent study has demonstrated that peripheral amylin treatment reduces the amyloid pathology in the brain of Alzheimer’s disease (AD) mouse models, and improves their learning and memory. We hypothesized that the beneficial effects of amylin for AD was beyond reducing the amyloids in the brain, and have now directly tested the actions of amylin on other aspects of AD pathogenesis, especially neuroinflammation. A 10-week course of peripheral amylin treatment significantly reduced levels of cerebral inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 61 publications
(76 reference statements)
0
48
1
Order By: Relevance
“…We and others have reported Ramp1 and Ramp3 are expressed in the mouse brain [38, 39]. Here, to confirm their expression in bEnd3 we first performed pilot studies to identify the amylin receptor expressed in these cells.…”
Section: Resultsmentioning
confidence: 94%
“…We and others have reported Ramp1 and Ramp3 are expressed in the mouse brain [38, 39]. Here, to confirm their expression in bEnd3 we first performed pilot studies to identify the amylin receptor expressed in these cells.…”
Section: Resultsmentioning
confidence: 94%
“…Using a microglial cell line, BV-2, we found that CD68 expression stimulated by LPS was downregulated by adding low concentrations of amylin. In contrast, CD68 expression was not influenced by the media addition of a high concentration of amylin (Wang et al, 2017). In the activated microglia cells, we validated that the amylin-induced attenuation of CD68 expression is mediated by binding to AmR by knocking-down the amylin receptor.…”
Section: Elucidating the Mechanism Of Amylin Effects On Learning And mentioning
confidence: 91%
“…Two well-documented markers for activated microglia, i.e., ionized calcium-binding adaptor (Iba-1) (Paquet et al, 2014; Zotova et al, 2013) and CD68 (Arnold et al, 2000), were examined in the brains of AD mouse models by immunostaining for the effects of amylin treatment on neuroinflammation in the AD brain. While amylin treatment significantly reduced the number of Iba-1+ microglia cells at the cortex, thalamus and hippocampus, amylin treatment modestly but significantly reduced the number of CD68+ microglia at the cortex region in AD mouse models (Wang et al, 2017; Zhu et al, 2017b). The expression levels of inflammatory cytokines IFNγ and IL-1β were also reduced by amylin treatment.…”
Section: Amylin Treatment Reduces the Core Ad Pathology In Ad Mouse Mmentioning
confidence: 94%
See 2 more Smart Citations